The Effect Of Marketing Mix On Visitor Satisfaction And Its Impact On Visitor Loyalty At Ragunan Wildlife Park - Yuliyati Nurmaya; Andini Nurwulandari (Jurnal Mantik, 2022)
The purpose of this study was to determine the effect of product, price, location, promotion, employees, process, physical environment on visitor loyalty through visitor satisfaction. The sample of this study was 300 visitors to Ragunan Wildlife Park aged 10-50 years, which were taken by non-probability sampling technique. Data analysis was performed using a structural equation model (Structural Equation Modeling - SEM). The results showed that product, price, location, employees, and physical environment had a direct and significant effect on visitor satisfaction, while promotion and process had an insignificant but not significant effect on visitor satisfaction. The variables of price, location, employees and physical environment have an indirect and significant effect on visitor loyalty through visitor satisfaction, while products, promotions, and processes have an indirect and insignificant effect on loyalty through visitor satisfaction.